Targeting LINC00665/miR-199b-5p/SERPINE1 axis to inhibit trastuzumab resistance and tumorigenesis of gastric cancer via PI3K/AKt pathway - Bingyu Wang; Wenbo Liu; Buyun Song; Yong Li; Yingying Wang; Bibo Tan (Non-coding RNA Research)
Long noncoding RNAs (lncRNAs) serve as critical mediators of tumor progression and drug resistance in cancer. Herein, we identified a lncRNA, LINC00665, associated with trastuzumab resistance and development in gastric cancer (GC). LINC00665 was highly expressed in GC tissues and high expression of LINC00665 was correlated with poor prognosis. LINC00665 knockdown was verified to suppress migration, invasion, and resistance to trastuzumab in GC. Furthermore, we found that LINC00665 participates in the infiltration of naive B cells, mast cells, and T follicular helper (Tfh) cells. Mechanistically, LINC00665 was confirmed to regulate tumorigenesis and trastuzumab resistance by activating PI3K/AKt pathway. LINC00665 sponged miR-199b-5p to interact with SERPINE1 expression, resulting in the increase of phosphorylation of AKt, thus participating in the PI3K/AKt pathway. To summarize, LINC00665 facilitated the tumorigenesis and trastuzumab resistance of GC by sponging miR-199b-5p and promoting SERPINE1 expression, which further activated PI3K/AKt signaling; this finding reveals a new mechanism by which LINC00665 modulates tumor development and drug resistance in GC.